INFORMATION AND ANALYTICAL SYSTEM AS A TOOL OF LIBRARY ACTIVITY OPTIMIZATION - Kobieliev, Oleksii; Pobizhenko, Volodymyr (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This article focuses on information and analytical systems as library activity optimization tools and on their basic functions and features